Effect of butylphthalide combined with citicoline on neurotrophic factors and oxidative stress after cerebral infarction - Chen, Zhongjun; Wu, Dongyun; Pan, Jiajun; Fan, Xinhong (Journal of Medical Biochemistry, 2025)
Background: To compare the effects of butylphthalide (BP) combined with citicoline (COPC) or vascular rehabilitation capsules (VRC), respectively, on vascular dementia (VD) after cerebral infarction (CI).Methods: 98 patients with VD after CI who were seen in our hospital from April 2020 to June 2022 were selected as the study population. Among them, 52 patients received BP combined with COPC (BP+COPC group), while the rest 46 received BP combined with VRC (BP+VRC group). Fasting venous blood was drawn from the patients before and after treatment, respectively, and the levels of nerve growth factor (NGF), neuron-specific enolase (NSE), brain-derived neurotrophic factor (BDNF), superoxide dismutase (SOD), malondialdehyde (MDA), Tumor necrosis factor-α (TNF-α), Interleukin-1β (IL-1β), and C-reactive protein (CRP) were measured. Cognitive and neurological improvements were assessed using the Loewenstein Occupational Therapy Cognitive Assessment (LOTCA) and the National Institute of Health stroke scale (NIHSS). In addition, the patient's cerebral hemodynamics were examined by CT.Results: After treatment, LOTCA increased in both groups and were higher in BP+COPC group than in BP+VRC group (P
Keywords: butylphthalide; citicoline; vascular dementia after cerebral infarction; inflammatory response; stress response